Cascade structure and event-level attribution of three-dimensional compound drought–heat events in China: contrasting meteorological and agricultural systems - Ben Niu; Yi Li; Shasha Han; Jinxuan Zhao; Darrell W.S. Tang; David M. Hannah (Journal of Hydrology, 2026)

Analysis of acoustic oceanographic data characterizing tidal and non-tidal current flux in a gulf–basin system - Omar A. Nimr; Ramy Y. Marmoush; Mohamed A. Oraby; Ahmed Gaweesh; Ahmed Balah; Darrell W. S. Tang (Frontiers in Marine Science, 2026)
Coastal currents arise from the combined influence of tidal and non-tidal processes such as wind forcing, density gradients, and Earth’s rotation. This study quantifies their relative contributions in the Gulf of Aqaba using velocity records from 10 Acoustic Doppler Current Profilers (ADCPs) deployed along the eastern shallow-water coast during April and May 2021. Harmonic least-squares analysis was used to separate the astronomical tidal current from the residual, and tidal form factors and rotary analysis characterized the tidal type and the ellipse properties of the principal constituents (M2, S2, K1, and O1). Non-tidal currents dominated throughout the study period, with the tidal-to-non-tidal speed ratio below unity at every station except one and a mean of 0.59. Tidal form factors classify the regime as mixed at almost all stations, with dominant contributions from the M2 and K1 constituents. Depth-averaged tidal ellipses are predominantly rectilinear and show marked spatial variability in speed and orientation, with the strongest currents where the coast narrows. Correlations between wind stress and the residual currents are moderate and organized predominantly along the coast, indicating that wind is a meaningful but partial driver, with much of the residual variability set by processes a local wind correlation cannot capture. These findings establish the predominance of non-tidal forcing in the coastal circulation of the Gulf of Aqaba and highlight the need for extended, co-located current and hydrographic records to resolve the full range of forcing in semi-enclosed stratified basins.

Polylactic acid microplastics regulate organophosphorus pesticide impacts on phosphorus bioavailability in soil-plant systems - Gaowei Tan; Lingling Ding; Darrell W.S. Tang; Yan Wang; Jing Yang; Hongyu Mu; Xiaomei Yang (Journal of Hazardous Materials, 2026)

Distinct interferences of conventional and biodegradable microplastics on adsorption of pesticide mixture in agricultural soils - Gaowei Tan; Darrell W.S. Tang; Osman Rima; Shijie Qin; Xuetao Guo; Violette Geissen; Xiaomei Yang (Environmental Pollution, 2026)

Effects of microplastic contamination on soil nitrogen and its bioavailability in soybean-maize rotation system - Xinkai Jia; Haoqing Li; Darrell W.S. Tang; Sha Xue; Enke Liu; Xiaomei Yang (Soil and Tillage Research, 2026)

Regional maize suitability based on soil water and salt content inversion by integrating machine and transfer learnings in Xinjiang - Shibin Wang; Yi Li; Tanyi Li; Wenlong Lu; Xingyun Qi; Xiangwen Xie; Renna Sa; Tongkai Guo; Alim Pulatov; Ishchanov Javlonbek; Darrell W.S. Tang; Kadambot H.M. Siddique (Soil and Tillage Research, 2025)

Pesticide transport under runoff-erosion potentially dominated by small sediments: A glyphosate and AMPA experiment - Xiaomei Yang; Vera Silva; Darrell W.S. Tang (Journal of Hydrology, 2025)

Climate and land use regulate vegetation–runoff interaction pathways in the three-river source region - Guiyuan Zhang; Darrell Tang; Song Li; Yurui Fan; Alim Pulatov; Aili Sun; Xingyun Qi; Licheng Wang; Yi Li (Journal of Environmental Management, 2025)

Soil C-N and microbial community were altered by polybutylene adipate terephthalate microplastics - Yao Yu; Yan Wang; Darrell W.S. Tang; Sha Xue; Mengjuan Liu; Violette Geissen; Xiaomei Yang (Journal of Hazardous Materials, 2025)

Co-occurrence of multiple contaminants: Unentangling adsorption behaviour in agricultural soils - Gaowei Tan; Darrell W.S. Tang; Vera Silva; Hongyu Mu; Shijie Qin; Osman Rima; Violette Geissen; Xiaomei Yang (Environmental Pollution, 2025)

Modeling microplastic transport through porous media: Challenges arising from dynamic transport behavior - Xiaomei Yang; Darrell W.S. Tang (Journal of Hazardous Materials, 2025)

Effects of polyethylene and poly (butyleneadipate-co-terephthalate) contamination on soil respiration and carbon sequestration - Mengyu Liu; Yao Yu; Ying Liu; Sha Xue; Darrell W.S. Tang; Xiaomei Yang (Environmental Pollution, 2025)

Phreatic zone wastewater irrigation: Sensitivity analysis of contaminant fate - Darrell W.S. Tang; Sjoerd E.A.T.M. Van der Zee; Ruud P. Bartholomeus (Journal of Hydrology, 2024)

Effects of LDPE and PBAT plastics on soil organic carbon and carbon-enzymes: A mesocosm experiment under field conditions - Xinkai Jia; Yu Yao; Gaowei Tan; Sha Xue; Mengjuan Liu; Darrell W.S. Tang; Violette Geissen; Xiaomei Yang (Environmental Pollution, 2024)

Restored vegetation dominates the decrease in surface and subsurface runoff on the Loess Plateau - Xin Yan; João Pedro Nunes; Jineng Sun; Darrell W.S. Tang; Yanxia Wen; Zhi Li (Journal of Hydrology, 2024)

Reactive contaminant infiltration under dynamic preferential flow - Darrell W.S. Tang; Helen K. French; Anton Leijnse; Ruud P. Bartholomeus; Sjoerd E.A.T.M. van der Zee (Journal of Hydrology, 2024)

Pesticide bioaccumulation in radish produced from soil contaminated with microplastics - Hui Ju; Xiaomei Yang; Darrell Tang; Rima Osman; Violette Geissen (Science of The Total Environment, 2024)

Managed phreatic zone recharge for irrigation and wastewater treatment - Darrell W.S. Tang; Sjoerd E.A.T.M. Van der Zee; Dominique M. Narain-Ford; Gé A.P.H. van den Eertwegh; Ruud P. Bartholomeus (Journal of Hydrology, 2023)

Ecological risk assessment of pesticides on soil biota: An integrated field-modelling approach - Hongyu Mu; Xiaomei Yang; Kai Wang; Darrell Tang; Wen Xu; Xuejun Liu; Coen J. Ritsema; Violette Geissen (Chemosphere, 2023)